Methods in human growth research (Cambridge University Press, 2004)
This volume is a review of up-to-date methods used in human growth research. Aimed at junior and senior researchers in human biology, anthropology, epidemiology and pediatrics involved in the analysis of normal and pathological growth and development data, it focuses on concepts, possibilities, limitations and applications